Structure and Evolution of the International Pesticide Trade Networks - Li, Jian-An; Xie, Wen-Jie; Zhou, Wei-Xing (Frontiers in Physics, 2021)
To meet the increasing demand for food around the world, pesticides are widely used and will continue to be widely used in agricultural production to reduce yield losses and maintain product quality. International pesticides trade serves to reallocate the distribution of pesticides around the world. We investigate the statistical properties of the international trade networks of five categories of pesticides from the view angle of temporal directed and weighted networks. We observed an overall increasing trend in network size, network density, average in- and out-degrees, average in- and out-strengths, temporal similarity, and edge reciprocity, indicating that the rising globalization of pesticides trade is driving the networks denser. However, the distributions of edge weights remain unchanged along time for the five categories of pesticides. In addition, all the networks are disassortatively mixed because large importers or exporters are more likely to trade with small exporters or importers. We also observed positive correlations between in-degree and out-degree, in-strength and out-strength, edge reciprocity and in-degree, out-degree, and in-strength and out-strength, while node's local clustering coefficient is negatively related to in-degree, out-degree, in-strength and out-strength. Since some structural and dynamic properties of the international pesticides trade networks are different from those of the international trade networks, highlighting the presence of idiosyncratic features of different goods and products in the international trade.